Principles of Macroeconomics for AP® Courses 2e - Greenlaw, Steven A.; Shapiro, David (Open textbook library., 2017)
Principles of Macroeconomics for AP® Courses 2e covers the scope and sequence requirements for an Advanced Placement® macroeconomics course and is listed on the College Board’s AP® example textbook list. The second edition includes many current examples and recent data from FRED (Federal Reserve Economic Data), which are presented in a politically equitable way. The outcome is a balanced approach to the theory and application of economics concepts. The second edition was developed with significant feedback from current users. In nearly all chapters, it follows the same basic structure of the first edition. General descriptions of the edits are provided in the preface, and a chapter-by-chapter transition guide is available for instructors.